PERTANGGUNG JAWABAN PELAKU TINDAK PIDANA DENGAN SENGAJA MENYEBARKAN INFORMASI YANG DITUNJUKAN UNTUK MENIMBULKAN RASA KEBENCIAN ATAU PERMUSUHAN INDIVIDU DAN KELOMPOK MASYARAKAT TERTENTU BERDASARKAN SARA - Hasan, Zainudin; Kholif Fadia, Nadhia (UNES Law Review, 2023)
Such as ethnicity, faith, race, gender, skin shade , defects, and plenty of more, as for the accountability of the perpetrators of hate speech crimes towards the defendant HS violating Article 45A paragraph (2) Jo. Article 28 paragraph (2) of law wide variety 19 of 2016 concerning facts and electronic Transactions, is punishable by imprisonment for 8 months, because the premise for the sentence is suitable and it's miles clean that the crime committed through the defendant HS is obvious. recommendations for law enforcers, especially the Panel of Judges, in prosecuting and enforcing instances of crook acts of hate speech, they should definitely look at and be aware of the advantage of the community, in order that selections that are conventional through each the defendant and the sufferer can produce peace and quietness for the community, but prioritizing criminal interests.